Peningkatan Kreativitas Siswa dalam Pembelajaran PPKn melalui Metode Problem Based Learning (PBL) - Nahar, Thohirotun; Hanifah, Afnan Nur; Anam, Khairul; Hanik, Elya Umi (MASALIQ, 2022)
This study aims to increase the creativity of third grade students of MI Miftahul Huda in the first semester of the 2021 academic year in the subject of PPKn Theme 3 Sub-theme 4 (KD 3.4 and 4.4) " Help Activities" through the Problem Based Learning (PBL) method. The procedures applied in each cycle include the following stages: 1) Planning, 2) Implementation, 3) Observation, 4) Reflection. The study consisted of 11 students who were divided into 3 groups. The data collection technique used a non-test technique and was carried out in 2 cycles. The increase starts from Pre-cycle activities with the classical approach reaching a percentage of 58.3% then Cycle I to cycle II with the results of the creativity of students who reach the creative category in the first cycle which is 65.3% and the second cycle of 86.1% which is a category Creative. Based on the results of the actions taken, it can be concluded that the application of the Problem Based Learning (PBL) method can increase the creativity of class III MI Miftahul Huda students in semester 1 of the 2021 academic year in the PPKn subject Theme 3 Sub-theme 4 "Help Help Activities".